The Role of interleukin 6 in chronic endometriosis and its impact on fertility - Rehana Batool, Sadia Ashiq, Hafiz Muhammad Nasrullah, Safoora Anjum, Muzamil Liaqat Ali, Nadeem Abbas (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Endometriosis represents a chronic inflammatory gynecological condition that contributes significantly to infertility among reproductive-aged women. Interleukin-6 (IL-6) has emerged as a central mediator in sustaining lesion growth, altering immunological balance, and impairing reproductive function. This experimental study aimed to investigate the association between IL-6 levels in serum and peritoneal fluid of women with chronic endometriosis and their fertility outcomes.